Principles of system approach in flight safety management in air traffic controller - Харченко, B.П.; Буцик, І.М.; Алєксєєв, О.М.; Колотуша, В.П.; Бабейчук, Д.Г. (Proceedings of National Aviation University (archive), 2010)
The modern conception of industrial flight safety management comes from the fact that only an observance of the set rules is not sufficient: it is necessary to probe the conditions of aviation activity, reveal the hazards, take necessary and sufficient measures on the declination of the risks, related to them,. till the acceptable level.